Perception of danger, coping strategies, and mental health in university population - Nicol Altamirano; Pablo Melo-Moreno; Felipe García (Interacciones)
Objective: This study aimed to relate life satisfaction and psychological distress to coping with the perception of criminal danger in university students. Method: Three scales were used: The Life Satisfaction Scale, the K-10 Psychological Distress Scale, and the Coping with Perceived Danger Scale. A total of 370 university students participated, of whom 65.4% were female, and 13.8% had experienced crime in the previous two years. Result: A positive and statistically significant relationship was found between coping with perceived danger, such as cautious avoidance (r=0.274, p ≤ 0.00), preventive coping (r=0.344, p ≤ 0.00), and extreme avoidance (r=0.207, p ≤0.00), with psychological distress. These relationships were even stronger for victims of crime. Women show higher levels of psychological distress and more cautious, avoidant and extreme coping strategies in the face of danger compared to men. Finally, a negative and significant relationship was observed between psychological distress and life satisfaction. Conclusion: It appears that regardless of whether a person has been a victim of crime in the last two years, perceptions of danger and strategies of cautious and even extreme crime prevention are related.